SWOT Analysis of Art Performance As City Promotional Strategy In Yogyakarta - Sari, Cahyani Tunggal; Subagyo, Hadi (Journal of Education Culture and Society, 2020)
Aim. Yogyakarta, a famous city in Indonesia, is well known for the Prambanan temple and its Ramayana Ballet performance. As the cultural and culinary city, Yogyakarta has been indirectly promoted by its cultural performances, such as Ramayana Ballet. The aims of the study were to identify the strengths, weaknesses, opportunities, and threats related to Ramayana Ballet Prambanan as a promotion strategy medium in Yogyakarta. Methods. This study used a historical approach in understanding the art performance in Ramayana Ballet Prambanan. Besides, this study used the data of tourists’ visits to Ramayana Ballet Prambanan, Yogyakarta. Results. This research shows that even though there are not many strengths of the Ramayana Ballet art performance, the opportunities related to this kind of promotional strategy compensate for the weaknesses and the threats. Conclusion. We can conclude that Ramayana Prambanan as an example of performance art in Yogyakarta has a positive value and provides a significant contribution to Yogyakarta tourism. These can be seen from the increase of tourist visitors to Ramayana art performance from 2008 to 2016. The art performance has become one of many promotional strategy choices in Yogyakarta.